PENGARUH PARTISIPASI ANGGOTA DAN PELAYANAN KREDIT TERHADAP KEBERHASILAN USAHA KOPERASI UNIT NAGARI (KUN) TALAGO II KABUPATEN 50 KOTA PAYAKUMBUH - Miftahul Husna Miftahul Husna; Sri Kartikowati Sri Kartikowati; Fenny Trisnawati Fenny Trisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to investigate the influence of member participation and credit services either simultaneously or partially on the success of the Cooperative Unit Nagari (KUN) Talago II District 50 Payakumbuh. The population in this study were all members of the Cooperative KUN Talago II numbering 1574 members. Random sampling random sampling method amounted to 94 members. Methods of data collection: questionnaire method and documentation. The method of data analysis is descriptive analysis percentage, Classical assumption test and multiple linear regression. The results showed that the participation of members and credit services simultaneously significantly to the success of cooperative efforts. Analysis of the factors examined in the study showed that the variables are the dominant influence on the success of the Cooperative Unit Nagari (KUN) Talago II District 50 Payakumbuh is a variable participation of members.Keywords: participation of members, credit services and business success